The dark side of digital learning: investigating technostress, academic disengagement and self-perception of academic performance among university students - Chong, Weiline Wei Ling (2025)
The COVID-19 pandemic has increased the use of digital technologies, making online and hybrid learning common among university students. While digital tools provide flexibility and easy access to learning, they also bring challenges. One key challenge is technostress, which is the stress caused by using technology. This study examines how compulsive technology use and information overload contribute to technostress and how technostress affects academic disengagement and student’s self-perception of academic performance.